The Value of Accounting Information on Stock Prices: A Systematic Literature Review - Rozhaiza Taha; Arni Karina; Muhammad Nur; Molina; Kumba Digdowiseiso (CV ODIS, 2023)
This literature study explores the complexity of the relationship between the value of accounting information (accounting profit, book value of equity, operating cash flow, and leverage) and stock prices in the context of the Indonesian financial market. The research methodology uses a Systematic Literature Review (SLR) with an in-depth analysis approach to related research. The research results show that the influence of accounting profits on stock prices is complex and influenced by external factors such as market conditions, regulatory policies and economic uncertainty. The relevance of the book value of equity as an indicator of company fundamentals influences stock prices, but variability depends on the industry and company size. Operating cash flow, although important, has a non-linear relationship with stock prices, influenced by macroeconomic factors and industrial policy. The leverage variable has an impact on a company's risk and resilience, although its direct influence on share prices is not always consistent. Global external factors and regional variability influence investors' perceptions of accounting information and stock prices. This research underscores the importance of considering industry context and external factors in evaluating the value of accounting information in making intelligent and informational investment decisions in complex financial markets